The transfer of land considered in relation to the rights of judgment creditors - Osborne, Robert W. (Statistical and Social Inquiry Society of Ireland, 1851)
Whilst the laws affecting property in these countries have wisely given to every one an unrestricted power of disposal over the property of his own creation, they have, at the same time, indirectly interfered with that privilege in practice, by throwing obstacles in the way of the alienation of land, injurious alike to the owner or debtor, and his creditor. As the power of transferableness forms one of the elements of the value of a commodity, any restriction on that power is a diminution of its value to the owner; whilst his creditor, from the period that he became entitled to claim the property, by advancing his money, his labour, or his goods, is injured in proportion to the delay and expense attendant upon its alienation. In considering, therefore, economically, the laws that affect the transfer of land, I propose to review them not only as they affect the possessor or the debtor, but also his creditor; and will endeavour to establish that whilst mortgages and charges created by the owner should be the only permanent incumbrances upon land, yet that it will not be incompatible with the speedy transfer and improvement of real property, that it should be liable to the claims of judgment creditors.
Read March 18th 1850
Keywords: Transfer of land; Creditors; 314.15